Comparative Efficacy of Inhaled and Intravenous Corticosteroids in Managing COVID-19-Related Acute Respiratory Distress Syndrome - Ahmed A. Abdelkader; Bshra A. Alsfouk; Asmaa Saleh; Mohamed E. A. Abdelrahim; Haitham Saeed (MDPI AG, 2024)
Acute respiratory distress syndrome (ARDS) is a life-threatening condition in which the lungs fail to provide sufficient oxygen to the body's vital organs. It is commonly associated with COVID-19 patients. Severe cases of COVID-19 can lead to lung damage and organ failure due to an immune response in the body. To mitigate these effects, corticosteroids, which are known for their anti-inflammatory properties, have been suggested as a potential treatment option. The primary focus of this study was to assess the impact of various corticosteroid administration methods on the outcomes of patients with COVID-19. Methods: The current study was conducted on COVID-19 patients divided into three groups. The first group was administered 6 mg of intravenous (IV) dexamethasone; the second group received 1 mg/kg of IV methylprednisolone (methylprednisolone); and the third group received budesonide respirable solution at a dosage of 1mg twice daily. The neubilizer used was a vibrating mesh nebulizer (VMN). All patients received standard care. We found that dexamethasone administered intravenously led to a significant reduction in C-reactive protein levels, surpassing the effectiveness of both IV methylprednisolone and inhaled budesonide. Oxygen saturation without mask change over time showed statistically significant differences (p = 0.004) in favor of the budesonide and dexamethasone groups for all days. Individuals who received methylprednisolone showed a significant decrease in mortality rate and an extended survival duration, with statistical significance observed at p = 0.024. The rest of the parameters, including ferritin, lymphocytes, total leukocyte count, platelets, hemoglobin, urea, serum potassium, serum sodium, serum creatinine, serum glutamic-pyruvic transaminase, serum glutamic-oxaloacetic transaminase, uric acid, albumin, globulin, erythrocyte sedimentation rate, international normalized ratio, oxygen saturation with flow, and oxygen flow, showed no statistically significant differences between the three drugs. In conclusion, treatment with IV methylprednisolone (1 mg/kg) resulted in a shorter hospital stay, decreased reliance on ventilation, and improved health outcomes for COVID-19 patients compared to using dexamethasone at a daily dosage of 6 mg or budesonide respirable solution at a dosage of 1mg twice daily.